2023
DOI: 10.1136/rapm-2023-104972
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the intertransverse process block: single or multiple injection? A randomized, non-inferiority, blinded, cross-over trial in healthy volunteers

Martin Vedel Nielsen,
Katrine Tanggaard,
Sophie Bojesen
et al.

Abstract: IntroductionThe intertransverse process block is increasingly used to ameliorate postoperative pain following a plethora of surgical procedures involving the thoracic wall. Nevertheless, the optimal approach and cutaneous extent of the sensory block are currently unknown. We aimed to further describe the intertransverse process block, single injection versus multiple injection, and we hypothesized that the single-injection intertransverse process block is a non-inferior technique.MethodsTwelve healthy male vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The ITP block is applied on the posterior side of the TPVS (retro-SCTL space) [ 15 ] in a modality described as paravertebral block by proxy. A single-injection ITP block has shown to be non-inferior to multiple injections in terms of anesthetized dermatomes demonstrating an involvement to a variable extent up to four levels [ 16 ]. In a real-life clinical practice study, which reflects the clinical reality more accurately than autopsy studies, Chen et al [ 17 ] found that compared with the ESP block, a single-injection ITP block yielded increased stability in the lateral and anterior chest wall block with improved anterior and intercostal spread although with a reduced cephalocaudal spread.…”
Section: Discussionmentioning
confidence: 99%
“…The ITP block is applied on the posterior side of the TPVS (retro-SCTL space) [ 15 ] in a modality described as paravertebral block by proxy. A single-injection ITP block has shown to be non-inferior to multiple injections in terms of anesthetized dermatomes demonstrating an involvement to a variable extent up to four levels [ 16 ]. In a real-life clinical practice study, which reflects the clinical reality more accurately than autopsy studies, Chen et al [ 17 ] found that compared with the ESP block, a single-injection ITP block yielded increased stability in the lateral and anterior chest wall block with improved anterior and intercostal spread although with a reduced cephalocaudal spread.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-transverse plane block is delivered to the posterior aspect of the thoracic paravertebral space (retro-superior costo-transverse ligament space), and is described as a `paravertebral-by-proxy´block [11]. A single-injection inter-transverse plane block has been demonstrated to be non-inferior in comparison to multiple injections in terms of anaesthetised dermatomes [12]. Chen et al observed that, compared to the erector spinae plane block, a single-injection inter-transverse plane block provides enhanced anterior and intercostal spread, albeit with reduced cephalocaudal spread [13].…”
Section: Discussionmentioning
confidence: 99%